(untitled) (Aporte Santiaguino, 2024)
Due to limited economic resources and easy access to soil as a building material, rural dwellers often build their homes with adobes, without applying anti-seismic design techniques or standards. This makes these homes highly vulnerable to earthquakes. In this context, the present research aimed to evaluate the behavior of adobe walls with seismic isolation through the use of shicras under monotonic lateral loading. To do this, the anti-seismic construction technique used by the Caral civilization was applied. Four treatments were designed: T0 (conventional overhang), T1 (overhang of shicras with 5-inch stones), T2 (overhang of shicras with 3-inch stones) and T3 (overhang of shicras with 1-inch stones) with three replications for each treatment. The field tests showed that walls 7, 8 and 9, corresponding to the T2 treatment, achieved the highest maximum displacements, with values of 12.83 mm, 12.12 mm and 13.09 mm in walls 7, 8 and 9, respectively. In addition, these walls withstood maximum lateral loads of 13.43 kN, 13.92 kN and 12.94 kN. The foundations built with stones wrapped in shicras acted as a roller-type insulation, providing rigidity in the vertical plane and flexibility in the horizontal.